Martensitic transformation cracking in high carbon steels for bearings. Issue 11 (23rd July 2016) - Bai, M. K.; Pang, J. C.; Wang, G. D.; Yi, H. L.
Abstract : Cracking generates usually due to the internal stress during martensitic transformation in high carbon steels, for instance the '1C–1.5Cr' bearing steels. A novel low-density '1.2C–1.5Cr–5Al' alloy has been designed recently for bearing application in previous research. The effect of morphology of martensite plates on the transformation cracking has been proposed and investigated in comparison between the '1.2C–1.5Cr–5Al' and '1C–1.5Cr' steels in this research. Based on the mechanisms proposed, the tendency for transformation cracking in the novel alloy with more carbon addition has been discussed compared with the '1C–1.5Cr' steel. This paper is part of a Themed Issue on Recent developments in bearing steels.